(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This study provides a comparative evaluation of emergency surgical outcomes in patients presenting with complicated abdominal malignancies, depending on the level of institutional specialization. A total of 100 patients were enrolled and divided into two comparable groups: those treated in a specialized oncology center and those managed in emergency surgical hospitals. Treatment in specialized oncology centers was associated with a significantly higher rate of radical procedures with lymph node dissection, accompanied by reduced postoperative complications (12% vs 28%), lower mortality (4% vs 14%), and improved 3-year survival (68% vs 42%). Based on the obtained findings, an optimized stepwise patient routing model involving emergency management, stabilization, and transfer to a specialized oncology center was proposed. The study emphasizes the clinical and organizational importance of integrating emergency and oncological care services to improve outcomes in this patient population.